EXPLORATION OF QUILTING TECHNIQUES ON WASTE CUTTINGS OF DENIM CLOTH TO MAKE WATCH STRAPS - Elsa Claudia Simandalahi; Ahmad Riyadi Swandhani; Yanuar Herlambang (RADJA PUBLIKA, 2025)
The textile industry produces large amounts of waste, including denim scraps that are often not optimally utilized. This study aims to explore the quilting technique as a creative method in using denim scrap waste into watch strap accessory products through an upcycling approach. The method used is an experimental-descriptive approach with stages of design exploration, manufacturing process, and evaluation of product results in terms of visual appearance, comfort, and usability. The results of the study show that the quilting technique is effective in processing denim waste into unique, artistic, and environmentally friendly products. The application of this technique within the upcycle framework not only reduces textile waste but also creates commercially valuable products with a new identity. This study is expected to contribute to the development of textile waste-based accessories and encourage sustainable design practices in the creative industry.